Child and Childhood: Preschool Teacher Candidates Reporting - Zeynep Berna Erdiller-Yatmaz; Ersoy Erdemir; Fetiye Erbil (Anı Publishing, 2018)
The purpose of the study is to understand the first-year preschool teacher education students' perceptions of child and childhood and to examine their child and childhood beliefs and child perceptions from social and historical viewpoints. This was a phenomenological study of the qualitative research approaches conducted with 16 undergraduate students enrolled in the preschool teacher education program of a state university. All participants were first-year students. Data were obtained through in-depth interviews that included semi-structured questions and were analyzed in order by open coding, axial coding and selective coding (Strauss & Corbin, 1998). Findings are presented under 5 major sub-headings; (1) Participants definitions of child and childhood regarding their own childhood, (2) adjectives with regard to childhood, (3) child adult dichotomy, (4) the concept of ideal child, and (5) their resources of perceptions of childhood. Findings are discussed within the context of childhood and education in light of the relevant social and historical literature.